Analysis of elementary school teachers’ knowledge of the deep learning approach in improving the quality of Physical Education learning - Pambudi, Aris Fajar; Santoso, Nugroho Puji; Kriswanto, Erwin Setyo; Utami, Nur Sita (Universitas Sriwijaya, 2026)
Research Background: The deep learning approach has the potential to improve the quality of physical education learning in elementary schools by strengthening deep understanding, critical thinking skills, and meaningful learning experiences. However, teachers' knowledge of this approach in the Special Region of Yogyakarta is still unknown. Research Objectives: This study aims to analyze teachers' understanding of deep learning and its implications for improving the quality of physical education learning in elementary schools. Method: This study uses a mixed methods approach with subjects being elementary school physical education teachers who are members of the KKG in the Special Region of Yogyakarta. The sampling technique used is purposive sampling with 30 teachers as respondents. Data were collected through observation, interviews, questionnaires, and documentation. The analysis was conducted through data reduction, data presentation, and conclusion drawing. The instruments used were a 15-item questionnaire, interview guidelines, and supporting documents. The ethical procedures included informed consent, assurance of respondent confidentiality, and the use of data for academic purposes only. Results: Based on the questionnaire, 33.3% of teachers strongly agreed, 40% agreed, 16.7% were unsure, 6.7% disagreed, and 3.3% strongly disagreed with the application of deep learning in PJOK learning. Overall, 73.3% of teachers agreed or strongly agreed, indicating a high level of acceptance of this approach. Conclusion: Many elementary school teachers in the Special Region of Yogyakarta responded positively to the application of deep learning in PE learning. This approach is considered capable of improving the quality of learning, despite obstacles such as limited time, facilities, and teacher understanding. The practical implications of this study emphasize the importance of continuous training, the provision of adequate facilities, and intensive assistance so that the implementation of deep learning does not remain merely a discourse but can be applied systematically and sustainably in PJOK learning in elementary schools.